A review of shockable arrhythmia detection of ECG signals using machine and deep learning techniques - Kavya, Lakkakula; Karuna, Yepuganti; Saritha, Saladi; Prakash, Allam Jaya; Patro, Kiran Kumar; Sahoo, Suraj Prakash; Tadeusiewicz, Ryszard (1947- ); Pławiak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
An electrocardiogram (ECG) is an essential medical tool for analyzing the functioning of the heart. An arrhythmia is a deviation in the shape of the ECG signal from the normal sinus rhythm. Long-term arrhythmias are the primary sources of cardiac disorders. Shockable arrhythmias, a type of life-threatening arrhythmia in cardiac patients, are characterized by disorganized or chaotic electrical activity in the heart`s lower chambers (ventricles), disrupting blood flow throughout the body.
Keywords: deep learning; defibrillation; electrocardiogram; feature extraction; shockable arrhythmias; ventricular fibrillation; ventricular tachycardia